Apoptotic and antitumor activity of death receptor antibodies require inhibitory Fcγ receptor engagement - Li, Fubin (National Academy of Sciences, 2012)
By virtue of their ability to induce apoptosis and regulate growth, differentiation, and cytokine responses, the tumor necrosis factor receptor (TNFR) superfamily members have emerged as attractive targets for anticancer therapeutics. Agonistic antibodies to apoptosis-inducing TNFRs, such as death receptor 5 (DR5), although displaying impressive activities against a variety of tumors in preclinical models, appear to be less active in clinical trials. We report that the in vivo apoptotic and antitumor activities of these antibodies have an absolute requirement for the coengagement of an inhibitory Fcγ receptor, FcγRIIB. Anti-DR5 antibodies of the type currently in clinical trials have weak FcγRIIB binding and thus are compromised in their proapoptotic and antitumor activities in both colon and breast carcinoma models. Enhancing FcγRIIB engagement increases apoptotic and antitumor potency. Our results demonstrate that Fc domain interactions are critical to the therapeutic activity of anti-DR5 antibodies and, together with previous reports on agonistic anti-CD40 antibodies, establish a common requirement for FcγRIIB coengagement for optimal biological effects of agonistic anti-TNFR antibodies.